2012
DOI: 10.2528/pierm12041801
|View full text |Cite
|
Sign up to set email alerts
|

Moving Target Tracking Using Time Reversal Method

Abstract: Abstract-Time reversal focusing of electromagnetic waves is investigated in case of source motion.We extract analytical formulation of uniformly moving source in presence of ideal time reversal cavity (TRC) and a more realistic model, time reversal mirror (TRM). Similar to the acoustic case, it has been observed that in case of moving point source spatial focusing is still achievable. Furthermore, we also investigate super resolution effects on time reversal (TR) focusing of moving source in continuous random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In recent years a variety of cavity optomechanical systems have been constructed and studied [2, 14,16,19,20,27,29,31,35,44,45,55,58,66,72,75,76,79], and phenomena such as mode cooling [16,30,71,75,76], self-excited oscillations [4,14,15,21,31,42,52,54,66] and optically induced transparency [40,59,70,82] have been investigated. In addition to applications in metrology [9,18] and photonics [5,34,89], the appeal of optomechanics lies in the potential for observation of macroscopic quantum behavior in mechanical systems [6,23,25,26,32,41,43,48,…”
mentioning
confidence: 99%
“…In recent years a variety of cavity optomechanical systems have been constructed and studied [2, 14,16,19,20,27,29,31,35,44,45,55,58,66,72,75,76,79], and phenomena such as mode cooling [16,30,71,75,76], self-excited oscillations [4,14,15,21,31,42,52,54,66] and optically induced transparency [40,59,70,82] have been investigated. In addition to applications in metrology [9,18] and photonics [5,34,89], the appeal of optomechanics lies in the potential for observation of macroscopic quantum behavior in mechanical systems [6,23,25,26,32,41,43,48,…”
mentioning
confidence: 99%
“…The replacement of water molecules with inhibitor molecules decreases the local dielectric constant as it involves replacement of higher dielectric constant to lower dielectric constant (Özcan et al, 2008). bonds (Solmaz et al, 2008;Bahrami and Hosseini, 2012). It is found that the ΔG ads values increase proportionally to the rise of temperature with values from -33.6 kJ mol -1 to -42.3 kJ mol -1 .…”
Section: Adsorption Isothermmentioning
confidence: 91%
“…In the present G o ads at 298, 308, 318 mol -1 of CPH inhibitor is not merely physisorption or chemisorption but involves both physisorption and electrostatic interaction that occurs between charged molecules and charged metal surface. Chemisorption is related to charge share or charge transfer from inhibitor molecules to the mild steel surfaces (Bahrami and Hosseini, 2012). Physisorption could also take place at the initial et al, 2008).…”
Section: Adsorption Isotherm and Free Energy Of Adsorptionmentioning
confidence: 99%